Personalised Mobile Picture Puzzle - Rusdi, Nur Syazwani (Universiti Teknologi Petronas, 2006)
Pictures taken using camera phone are usually available for printing, sending to others via e-mails or MMS and if the pictures are copied to computer, the pictures can be modified using special software for image development. Therefore, a game that called Picture Puzzle will take the advantage of the pictures taken using camera phones in order to multiuse those pictures. The main objective of project is about developing a mobile game application in order to multiuse the picture taken using camera phone. The project had involved research and study on Mobile API, RMS and TiledLayer class from Game API with the purpose of developing the mobile game application. The project had consisted five main phases which are Planning, Analysis, Design, Development and Implementation. The Picture Puzzle will be displayed the picture taken as a scrambled grid and then the user will have to unscramble the picture puzzle. When the user manages to unscramble the puzzle, the game is completed. As conclusion, the project had able to achieve its objectives and the game application will be able to run as expected when it is implemented on the handphone.